Gene polymorphisms of SFTPB rs7316, rs9752 and PAOX rs1046175 affect the diagnostic value of plasma Pro‐SFTPB and DAS in Chinese Han non–small‐cell lung cancer patients. Issue 9 (23rd April 2019) - Wang, Kun; Huang, Qiubo; Zhao, Guangqiang; Yang, Jiapeng; Yang, Kaiyun; Huang, Yunchao
Abstract: Plasma pro‐surfactant protein B (pro‐SFTPB) and N1, N12‐diacetylspermine (DAS) can be used as markers for the diagnosis of non–small‐cell lung carcinoma (NSCLC). Whether the genetic diversity affects the application value of Pro‐SFTPB and DAS as a diagnostic marker for NSCLC is still unknown. This study aims to explore the relationship between SFTPB rs7316, rs9752 and PAOX rs1046175 gene polymorphisms and the diagnostic value of plasma Pro‐SFTPB and DAS in patients with Chinese Han lung cancer. SFTPB rs7316, rs9752 and PAOX rs1046175 genotypes were analyzed by direct sequencing in 425 patients with NSCLC and 425 controls, and the levels of Pro‐SFTPB and DAS in plasma were determined by enzyme‐linked immunosorbent assay (ELISA). The area under the curve (AUC) of the SFTPB rs7316 locus TT genotype for the diagnosis of NSCLC was 0.758, and the AUC of the TC/CC genotype for the diagnosis of NSCLC was 0.872. The AUC of the SFTPB rs9752 locus GG genotype for the diagnosis of NSCLC was 0.935, and the AUC of the GC/CC genotype for the diagnosis of NSCLC was 0.648. The AUC of the PAOX rs1046175 locus GG for the diagnosis of NSCLC was 0.669, and the AUC of the GC/CC genotype for the diagnosis of NSCLC was 0.749. In conclusion, SFTPB rs7316, rs9752, and PAOX rs1046175 gene polymorphisms affect the diagnostic value of plasma Pro‐SFTPB and DAS in patients with Chinese Han NSCLC. Abstract : The current study clearly demonstrates that the gene polymorphisms of SFTPB rs7316, rs9752 and PAOX rs1046175 locus affect the diagnostic value of plasma Pro‐SFTPB and DAS for non–small‐cell lung carcinoma in Chinese Han patients.